The Effect Simba Puzzle on Student's Self Efficacy Level in Flood Disaster Preparedness - Juan Prasetyo Pamula; M Hanif Prasetya Adhi; Meida Laely Ramdani; Ninuk Angelia (LP3M Universitas Muhammadiyah Tasikmalaya, 2025)
Floods are among the most frequent natural disasters in Indonesia, including in Sirau Village, Kemranjen District, Banyumas Regency, Central Java Province. These recurring floods, occurring almost annually, result in significant infrastructure damage, economic losses, and health challenges for the affected communities. Moreover, the lack of preparedness, particularly among children, remains a critical issue. Preliminary interviews with the principal and students at MI Muhammadiyah 01 Sirau revealed that most students exhibit low levels of self-efficacy regarding flood disaster preparedness. This study employed a quantitative pre-experimental design with a one-group pretest-posttest approach. The population comprised 40 fourth- and fifth-grade students from MI Muhammadiyah 01 Sirau, with total sampling used as the sampling method. Research instruments included the SIMBA (Siaga Menghadapi Banjir) puzzle and a self-efficacy questionnaire. Data were analyzed using the Wilcoxon test. The analysis revealed a significant improvement in students' self-efficacy levels after using the SIMBA puzzle, with a p-value of 0.001 (p 0.005). This finding confirms that the SIMBA puzzle effectively enhances students' confidence and preparedness in dealing with flood disasters. The SIMBA (Siaga Menghadapi Banjir) puzzle is an effective educational tool for improving self-efficacy among school-age children in flood disaster preparedness.